Workshop report (Journal of Face Aesthetics, 2024)
On January 5, 2024 were organized by the Polish Society for Facial Aesthetics, in cooperation with the Department of Cosmetology of the Academy of Applied Sciences in Pila, headed by Dr. Agata Skalska‑Stochaj, Workshop on Facial Care, reminiscences after the conference "Fatigue – its role and influence on the appearance of the face", which was held in September 24, November 2023. The workshop was organized at the urgent request of conference participants, both doctors and dentists, and other people interested in facial aesthetics.
Keywords: workshop; report; Polish Society for Facial Aesthetics